Survival Analysis of Patients with Osseous Malignant Vascular Tumors: Results of the Surveillance, Epidemiology, and End Results (SEER) Database from 1973 to 2015 - Wang, Wei (Med Sci Monit, 2019)
BACKGROUND: Osseous malignant vascular tumors (OMVTs) are rare lesions. Moreover, the prognostic determinants of OMVTs have not been reported. This study aimed to present epidemiological data and analyze the prognostic factors of survival in OMVT patients. MATERIAL/METHODS: OMVT patients who were diagnosed between 1973 and 2015 were screened using the Surveillance, Epidemiology, and End Results (SEER) program database, with special attention paid to osseous hemangiosarcoma (OAS) and osseous hemangioendothelioma (OHE). We assessed the prognostic values of cancer-specific survival (CSS) and overall survival (OS) rates with a Cox proportional hazards regression model and univariate and multivariate analyses. OS and CSS curves were obtained using the Kaplan-Meier method. RESULTS: A total of 202 cases were selected from the SEER database. The specific histopathological diagnoses were osseous hemangiosarcoma (n=127) and osseous hemangioendothelioma (n=75). Among OMVT patients, histology was an important factor in determining survival. Using multivariate analysis, old age, distant tumor stage, surgery, and low tumor grade were predictors of OS for OAS patients. Old age, surgery, and low tumor grade were predictors of CSS. Using multivariate analysis, old age and surgery were predictors of OS and CSS for OHE patients. CONCLUSIONS: This study is the largest population-based study to show the demographic characteristics and analyze the prognosis of OMVT patients. Independent predictors of OS for patients with AS included old age, distant tumor stage, low tumor grade, and surgery. Old age, surgery, and low tumor grade were also predictors of CSS for patients with OAS. Independent predictors of CSS and OS for patients with OHE included old age and surgery.